2020
DOI: 10.3389/fmars.2020.00134
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Approach to Explore the Background Benthic Fauna Around a Hydrothermal Vent and Their Larvae: Implications for Future Mining of Deep-Sea SMS Deposits

Abstract: Seafloor massive sulfide (SMS) deposits are commonly found at hydrothermal vents and recently gained the special interest of mining industries. These deposits contain valuable metals and methods are currently developed to mine deep sea SMS deposits. However, excavation of SMS deposits potentially pose a threat to benthic life at the mining site itself, and also in the surrounding environment with plumes of suspended sediment and fine-grained SMS debris created during deep sea mining activities being highlighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 80 publications
2
9
0
Order By: Relevance
“…Especially at station 40, located on the Rainbow Ridge, the Ca / Fe molar ratio is significantly higher than at the other stations. This is in line with observations by Khripounoff et al (2001) and Cave et al (2002), who also found that the relative Ca concentration in settling parti-cles and the sediments is lower close the Rainbow vent field and increases as the Fe concentration decreases when the plume disperses. Since Ca is naturally present in high abundances in pelagic skeletal carbonate that rains down from the overlying water column and Fe is mainly present as a hydrothermal component, the Ca / Fe molar ratio could be an indicator for the extent of the hydrothermal influence.…”
Section: Geochemical Gradients Within the Hydrothermal Plumesupporting
confidence: 92%
See 2 more Smart Citations
“…Especially at station 40, located on the Rainbow Ridge, the Ca / Fe molar ratio is significantly higher than at the other stations. This is in line with observations by Khripounoff et al (2001) and Cave et al (2002), who also found that the relative Ca concentration in settling parti-cles and the sediments is lower close the Rainbow vent field and increases as the Fe concentration decreases when the plume disperses. Since Ca is naturally present in high abundances in pelagic skeletal carbonate that rains down from the overlying water column and Fe is mainly present as a hydrothermal component, the Ca / Fe molar ratio could be an indicator for the extent of the hydrothermal influence.…”
Section: Geochemical Gradients Within the Hydrothermal Plumesupporting
confidence: 92%
“…Interestingly, near-bottom water (and sediment) community assemblages were distinct from the below-plume and other water column communities. This could imply (1) that there is little "fallout" from the plume at distance from the vent, which is in agreement with sediment trap observations by Khripounoff et al (2001); that (2) plume-specific bacteria die off due to lack of energy sources and DNA degrades before reaching the seafloor; and that (3) microbes are more abundant in the near-bottom waters, either naturally or through mechanical disturbance resuspending sediment during the coring process, outnumbering groups that have been mixed in from overlaying water. Despite the presence of a plume and precipitation, a difference between the sea floor and the water column biotopes is present, consistent with global broadscale non-vent benthic-pelagic patterns (Zinger et al, 2011).…”
Section: Plumes Influence On the Water Column Chemical And Microbial supporting
confidence: 84%
See 1 more Smart Citation
“…Despite their remoteness, deep-sea habitats have been relatively well-characterized with eDNA. Several deep-sea eDNA studies explored diversity in abyssal plains, while others targeted seamounts (e.g., Kitahashi et al, 2020;Laroche et al, 2020), canyons (Andruszkiewicz et al, 2017;Guardiola et al, 2015), hydrothermal vents (e.g., Klunder et al, 2020), and cold seeps (Macheriotou et al, 2021). Artificial habitats, such as floating marine litter and shipping ballast water, have also been the focus of DNA metabarcoding research (Ibabe et al, 2020).…”
Section: Edna Across a Wide Range Of Habitatsmentioning
confidence: 99%
“…The species inhabiting this particular habitat may be exposed to mining-related sediment plumes. By looking at benthic communities with eDNA from sediment and water in the vicinity of natural plumes, Klunder et al (2020) reported the fauna to be heavily influenced by the plume's fall out and communities varying over small spatial scales, which may hinder their restoration after mining activities. Cowart, Murphy and Cheng (2018) used eDNA to study recolonization dynamics of benthic communities associated with hard-substrata after an experimentally induced faunal clearance.…”
Section: Application Of Edna For Impact Assessment Biodiversity Monit...mentioning
confidence: 99%